MEASURES FOR IMPROVING THE METHODS OF EDUCATING YOUTH IN THE NATIONAL SPIRIT BASED ON MUSIC CIRCLES - Kasimjonova Marjona Alisher kizi (Scholars Digest Publishing, 2023)
This article provides detailed information about the organization of music clubs, pedagogical technologies for improving the pedagogical skills of teachers, methods of improving the methods of educating students in the national spirit on the basis of music clubs.
Keywords: culture, circle, pedagogical skills, demand, supply, art, music, education, interest.